Space‐Time Isogeometric Analysis of Parabolic Diffusion Problems in Moving Spatial Domains. Issue 1 (18th November 2019) - Kyas, Svetlana; Langer, Ulrich; Repin, Sergey
Abstract: This paper addresses locally stabilized space‐time isogeometric (IgA) schemes for parabolic diffusion problems in moving spatial domains. It generalizes the results of our preceding works for problems in fixed spatial domains. We present functional a posteriori error estimates and study adaptive numerical procedures based on them and on truncated hierarchical B‐splines.